(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The article considers the impact of climate change on the yield of sunflower hybrids in the forest-steppe zone of the Kharkiv region during 2022–2025. The aim of the study was to establish the relationship between agroclimatic indicators — total precipitation, total active temperatures (above 10 °C), and the hydrothermal coefficient (HTC) — and the yield of five sunflower hybrids: SI “Chester,” P64LL129, SI “Lascala,” NK “Kondi,” and P64LP130. The research was conducted on farms in the Berestinsky district, where the conditions for sunflower vegetation during the analyzed period were characterized by a sharp contrast in temperature and humidity. The analysis revealed a trend toward rising temperatures and decreasing precipitation during 2022–2025, which is confirmed by a decrease in the hydrothermal coefficient from 1.1 to 0.4. These changes indicate a gradual increase in aridization of the climate in the region. Sunflower yields decreased on average from 3.6 t/ha (2022) to 2.4 t/ha (2025), which correlates with the deterioration of moisture conditions. The highest yield stability indicators were observed in the NK Kondi and P64LP130 hybrids, which indicates their better adaptation to higher temperatures and moisture deficiency. Correlation analysis showed a close direct relationship between precipitation and hybrid yield (r = 0.87–0.99) and a negative relationship between the sum of active temperatures and yield (r = –0.68 to –0.89). The hybrids SI “Chester” and SI “Lascala” showed the greatest sensitivity to climatic fluctuations, while the P64LP130 hybrid, grown using Clearfield technology in 2024–2025, showed a weak correlation with climatic indicators, which may indicate greater stability and potential resistance to extreme weather conditions. The results confirm that in modern climatic conditions, it is advisable to use drought-resistant hybrids and adaptive cultivation technologies aimed at maximizing soil moisture conservation. Given the increase in the cost of sunflower seeds (from 13.6 to 26.8 thousand UAH/t in 2022–2025), the issue of economic efficiency in the selection of hybrids and technologies that ensure stable yields under climatic risks is also relevant. The research conducted deepens the understanding of the adaptive potential of modern sunflower hybrids in the Forest-Steppe zone of Ukraine and can be used to optimize crop structure and predict yields, taking into account climate change trends.